2014
DOI: 10.2967/jnumed.113.126409
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Metabolic Network Modulation Between Capsulotomy and Deep-Brain Stimulation for Refractory Obsessive-Compulsive Disorder

Abstract: Around 7%-10% of patients with obsessive-compulsive disorder (OCD) are refractory to first-line treatment. Neurosurgical approaches are available such as capsulotomy or deep-brain stimulation (DBS). There is strong evidence for central involvement of the corticostriatopallidothalamocortical (CSPTC) circuit in OCD, but the exact mechanism through which these interventions lead to clinical improvement and potential differences in network modulation are not fully understood. Methods: In total, 13 capsulotomy pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…Electrical stimulation significantly decreased freezing, but electrolytic lesions had superior effects on both freezing and startle values. 55, 56 However, DBS holds several advantages over permanent lesions, as it allows for adjustable, individual parameter settings to achieve optimal therapeutic effects with minimal side effects. From a clinical perspective, a reversible and adaptable neurosurgical procedure is preferable, but further research will be pivotal to optimize DBS effects and evaluate the potential of this treatment option for patients suffering from pathological anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation significantly decreased freezing, but electrolytic lesions had superior effects on both freezing and startle values. 55, 56 However, DBS holds several advantages over permanent lesions, as it allows for adjustable, individual parameter settings to achieve optimal therapeutic effects with minimal side effects. From a clinical perspective, a reversible and adaptable neurosurgical procedure is preferable, but further research will be pivotal to optimize DBS effects and evaluate the potential of this treatment option for patients suffering from pathological anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of improvement of depression and anxiety in this study were in line with those reported by previous studies (44.7% to 68.1% for HAM-D and 48.4% to 77.0% for HAM-A). [28][29][30] Interestingly, we observed significant improvements in depression and anxiety symptoms as early as 1 week after MRgFUS. Another recent study reported a significant reduction in HAM-D and HAM-A scores as early as 2 weeks after bilateral capsulotomy.…”
Section: Discussionmentioning
confidence: 58%
“…Lastly, Suetens et al . have shown that DBS at the bed nucleus of the stria terminalis decreased regional cerebral blood flow in the anterior cingulate and the prefrontal and orbitofrontal cortices [78]. There are only a few neuroimaging studies that investigate metabolic changes after rTMS in OCD.…”
Section: Discussionmentioning
confidence: 99%